The prospect and challenges of Knowledge Intensive Services (KIS) in the North Corridor Economic Region: A model towards sustaining economic growth. - Sheikh Dawood, Sharifah Rohayah (Universiti Sains Malaysia, 2016)

(untitled)
This research investigates the interrelations of urbanisation and globalisation, and the structural changes in the economy towards knowledge intensive services and industries in the northern region of Malaysia. The analysis considered the prospect and challenges of knowledge intensive services (KIS) in serving and sustaining the needs of the manufacturing and services sector in this corridor. Focus was given to the concept of 'knowledge economy' as a prelude to regional growth and development.